A study of Fermi hole and partial Fermi hole for Li- and C-Atoms in different states 1s 2p, 1s 3p, 1s 3d and 2s 2p - M., Naeemah Ch. (Iraqi Journal of Physics, 2019)
The electron correlation effect for inter-shell have been analysed in terms of Fermi hole and partial Fermi hole for Li-atom in the excited states (1s2 3p) and (1s2 3d) using Hartree-Fock approximation (HF). Fermi hole Δf(r12) and partial Fermi hole Δg(r12 ,r1) were determined in position space. Each plot of the physical properties in this work is normalized to unity. The calculation was performed using Mathcad 14 program.